Colonial historiography : a non-western perspective of the Larut Wars (1861-1875) - Asilatul Hanaa Abdullah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
British historians and orientalists during the peak of colonialism, was Eurocentric. This worldview shaped their historical writings of the Malays as being in a state of belligerency and was ruled by despots. The British emphasized that colonialism was necessary in order to carry out their civilizing missions and rescuing the Malays; thus, justifying their intervention in Larut Wars. This Eurocentric worldview undeniably lacked neutrality and objectivity. Erroneous orientalists’ Eurocentric ideas affected the historiography and narratives of Larut Wars. Eurocentricism in studying Malay history focused on British being the saviour and was pro-colonial. Hence, this created a biased narrative in the Larut wars. This narrative was used to legitimise colonialism by orientalists. This research aims to study; i) the effect of Eurocentrism in the historiography of Larut wars, ii) how the British Eurocentric perceptions evaluates the socioeconomic situation of the Malays and iii) to access the British Colonial documents and the influence on the narrative of Larut Wars. Qualitative research involving archival records was conducted and these records were later analyzed for Eurocentrism, which was further deconstructed and reconstructed into a Malay-centric perspective. The colonial historians or orientalists were Eurocentric in their views as a consequence from a formative worldview that started in Europe. The narrative was written based on primary sources that were Eurocentric which definitely would affect the secondary sources that formed this narrative. After these primary and secondary narratives were deconstructed, a new objective narrative was formulated presenting the history of Larut in the Malay context. Eurocentric ideas of modernism were erroneous due to the element of human pre-conception, thus even historical text would not necessarily represent the actual context of the conditions of the Malays. This incomplete truth can be refuted by using the Malay text proving Malays were not belligerent people ruled by despots but rather a civilization in its own.